Reassessing the NYHA classification for heart failure: a comparison between classes I and II using cardiopulmonary exercise testing. (14th October 2021) - Zimerman, A; Cardoso De Souza, G; Engster, P; Spier Borges, M; Ulrich Schaan, T; Pilar, I; Stein, R; Fonteles Ritt, L.E; Donelli Da Silveira, A; Rohde, L.E
Abstract: Background: The New York Heart Association (NYHA) functional classification has evolved to become a major determinant of eligibility to medical interventions and clinical trials, but its reliability to discriminate patients with mild heart failure (HF) has been questioned by studies that demonstrated a major overlap in self-reported symptoms and laboratory markers between NYHA classes I and II. Purpose: To assess the reliability of NYHA classification by comparing cardio-pulmonary exercise test (CPET) results and its overlap between HF patients classified as NYHA I and II. Methods: We retrospectively analyzed data from HF patients who underwent CPET in 3 medical centers in Brazil. NYHA class was defined as recorded on CPET day or during the previous clinical visit. Inclusion criteria were diagnosis of HF, age ≥16, and NYHA class I or II. We analyzed overlap between kernel density estimations for the percent-predicted peak VO2, minute ventilation/carbon dioxide production (VE/VCO2) slope, and oxygen uptake efficiency slope (OUES) in patients in NYHA classes I and II. Categorical variables were compared using chi-square tests. Results: We included 684 patients, of which 42% (284) were classified as NYHA I. Mean age was 56.1 years; 44% (303) were female and mean left ventricular ejection fraction was 36% (±14.2%). Regarding CPET measures, mean global percent-predicted peak VO2 was 56.6% (±26.1%), VE/VCO2 slope was 38.8 (±10.2), and OUES was 1.50 (±0.59). Kernel density overlap between NYHA classes I and II was considerable: 83% for percent-predicted peak VO2, 89% for VE/VCO2 slope, and 85% for OUES (Figure 1). There was no significant difference between NHYA I and II in CPET indicators of poor prognosis: percent-predicted peak VO2 <50% was present in 53% vs. 48% of patients classified as NYHA I and II, respectively (p=0.15); VE/VCO2 slope >36 in 54% vs. 57% (p=0.39); and OUES <1.4 in 46% vs. 48% (p=0.51). Conclusions: HF patients classified as NYHA I and II overlap substantially in objective measures of functional capacity assessed by CPET. These findings suggest that NYHA classification is a poor discriminator of cardiopulmonary capacity among patients with mild HF, and raise questions about its use as a benchmark to guide HF therapy. Funding Acknowledgement: Type of funding sources: None.